2019
DOI: 10.1039/c9ra08960h
|View full text |Cite
|
Sign up to set email alerts
|

Dual functional oyster shell-derived Ag/ZnO/CaCO3 nanocomposites with enhanced catalytic and antibacterial activities for water purification

Abstract: Oyster shell was used as an efficient template for synthesis Ag/ZnO/CaCO3 nanocomposites, which showed the enhanced catalytic and antibacterial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…S. mutans was cultured in BHI broth (Brain Heart infusion broth, Oxoid Ltd, Basingstoke, Hants, UK), and L. acidophilus was cultured in MARS broth (Methicillin-resistant Staphylococcus aureus broth, Huankai Microbial, Guangzhou, China). Conduct experiments with reference to the relevant literature on the subject [25][26] [29]. The bacterial suspension was uniformly spread on agar plates, and tablets made of samples were each placed on the media for inhibition zone experiment.…”
Section: Antibacterial Potential Of Ag/zno/oyster Shellmentioning
confidence: 99%
“…S. mutans was cultured in BHI broth (Brain Heart infusion broth, Oxoid Ltd, Basingstoke, Hants, UK), and L. acidophilus was cultured in MARS broth (Methicillin-resistant Staphylococcus aureus broth, Huankai Microbial, Guangzhou, China). Conduct experiments with reference to the relevant literature on the subject [25][26] [29]. The bacterial suspension was uniformly spread on agar plates, and tablets made of samples were each placed on the media for inhibition zone experiment.…”
Section: Antibacterial Potential Of Ag/zno/oyster Shellmentioning
confidence: 99%
“…[73][74][75] An Ag/Zn 2 O/CaCO 3 composite constructed using oyster shells as a solid catalytic support exhibited excellent performance at reducing 4-nitrophenol, with a conversion rate of 97.6% within 8 min. 76 Shells have good application prospects in the field of catalysis, but their catalytic applications are usually based on calcium oxide. The calcination transformation process consumes additional energy and generates exhaust gas emissions.…”
Section: Catalysts and Supportsmentioning
confidence: 99%
“…Therefore, the ideal bone cement should have the ability to promote the osteogenic activity of osteoblasts while inhibiting bacterial growth. , Antimicrobial drugs can help address the challenges posed by drug-resistant bacterial infections . ZnO is an antimicrobial material that has been widely used and demonstrated excellent antibacterial effects. Felice et al prepared a polycaprolactone/ZnO/HA scaffold and found that after doping with ZnO, the scaffold exhibited good antibacterial activity and promoted early cell mineralization induction by the scaffold at a high concentration of ZnO.…”
Section: Introductionmentioning
confidence: 99%